Pengembangan Parsing PCPATR Sebagai Preservasi Bahasa dan Sastra Banjar - Novia Winda; Ali Muhammad (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
Banjar Mantra is part of the Banjar language and literature in the form of words recited orally by certain people. Mantras are considered to have magical powers for supernatural powers and curses. This study aims to develop a sentence parsing device as a Language and Literature Preservation of Banjar using a sentence parsing application (parse PC-PATR). Parse PC-PATR is a sentence parsing application that will produce a pattern tree to represent the syntactic structure of sentences based on the Banjar language grammars. The problem in this research is that the mantra corpus uses the old genre of Banjarese language and literature. Words in the old genre are currently not widely used in communication by the Banjar people. On the other hand, the absorption of Arabic also presents its own problems. Finally, it is difficult to find the availability of experts who still preserve the Banjar mantra. This research used the ADDIE method with 20 Banjar mantras as test sentences and involved 3 committees of linguists as examiners. The research results showed that the naturalness of the test sentences was as low as 6%. The average parsing tree suitability percentage is 98%. This shows that the sentence parser is acceptable even though the naturalness of the test sentences is only 18% on average.